Measuring Rotation and Manure Effects in an Iowa Farm Soil Health Assessment. (1st January 2019) - Karlen, Douglas L.; Obrycki, John F.
Abstract : Core Ideas: Farms with known management histories contribute to soil health research. Rotation‐based systems may increase soil organic carbon when combined with appropriate tillage. Inherent soil properties must be considered in soil health assessments. Rotation effects were more noticeable than manure effects on soil health groupings. Data from on‐farm sites with known management histories are needed to quantify soil biological, chemical, and physical properties influencing carbon stocks and soil health. Surface (0–15 cm) and deep core (0–122 cm) soil samples were collected from fields under two rotations in Boone County, IA. The first was a 5‐yr corn [ Zea mays (L.)], soybean [ Glycine max (L.) Merr.], corn, oat [ Avena sativa (L.)], and alfalfa [ Medicago sativa (L.)] rotation to which 0, 18, or 36 Mg ha −1 of a manure/biosolids mixture was applied prior to planting corn. The second was an 8‐yr rotation with 6 yr of mixed grass and legume pasture followed by corn and an oat crop within which the pasture mixture was reestablished. Soil samples were collected evenly across the predominant soil map units (SMUs). Bulk density (BD), soil organic C (SOC), water‐stable aggregates (WSA), microbial biomass carbon (MBC), pH, Mehlich‐3 and diethylenetriaminepentaacetic acid (DTPA) extractable nutrients, electrical conductivity (EC), and nitrogen (total‐, NH4 –, and NO3 –N) were measured. Surface SOC data were consistent with Soil Survey values for the various SMUs. Crop rotation effects were more noticeable than manure/biosolid application rate effects. Data from this study were combined with previously published SOC data in Iowa. Results suggest extended rotation systems or those with cover crops may increase SOC 8 ± 4 g kg −1 compared to corn–soybean rotations (33 vs. 25 g kg −1 ). This study provides on‐farm reference values for soil health assessment tools and draws attention to the importance of inherent soil properties for these assessments.